Restitutio in Integrum in Criminal Regulation of Restitution for the Victims of Criminal Acts - Celine Endang Patricia Sitanggang; Jennifer Kurnia Putri; Albertus Hansen Setyabudi; Sheyla Alif Alfiana (Journal of Law, Politic and Humanities, 2024)
This study aims to determine the application of the Restitutio in Integrum principle in Indonesian laws and regulations governing restitution to victims of criminal acts. It is currently known that the weakness of restitution execution power in Indonesia has made the fulfillment of restitution to victims difficult to realize. This is because there is no binding force, so that the implementation of restitution is oriented towards the goodwill of the perpetrator of the crime. The research method used in this article is normative juridical with statute approach and conceptual approach. This study argues that restitution arrangements in various laws and regulations in Indonesia do not accommodate forced efforts if the perpetrators of criminal acts do not carry out restitution. In this case, the lacuna results in the difficulty of executing payments that should be received by victims of criminal acts. Therefore, it is necessary to strengthen the application of the principle of restitutio in integrum which is studied through substance, structure, and legal culture as an effort to realize protection as well as justice for victims of inclusive criminal acts.